Pengembangan Media Video Animasi Merawat Tanaman Untuk Mengenalkan Karakter Peduli Lingkungan Anak Usia Dini - Khusniyati Masykuroh; Anisah Anggrainy (UNIB Press, 2024)
Environmental awareness among students is an important aspect in efforts to preserve the environment and sustainable development. The character of caring for the environment needs to be taught from an early age because it shapes an individual's daily behavior and attitudes towards the environment, including efforts to prevent and repair damage to nature. This research aims to develop animated video media about the importance of caring for plants to introduce the character of caring for the environment. This study is development research using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model which involves experts as validators. The validation results carried out by PAUD Material Experts, Animation Media Experts, Language Experts and Practitioners show an average percentage of 93.75%, which means that the media has a very high level of validity. Thus, this animated video is considered suitable for use as a learning medium to introduce environmentally caring characters to young children.